2021
DOI: 10.1177/1049909121994299
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Personalized Virtual Reality in Palliative Care: A Feasibility Trial

Abstract: Background: Virtual Reality can help alleviate symptoms in a non-palliative care population. Personalized therapy can further alleviate these symptoms. There is little evidence in a palliative care population. Aim: To understand the feasibility of repeated personalized virtual reality sessions in a palliative care population. Design: A feasibility randomized control trial. Intervention: personalized virtual reality, Control: non-personalized virtual reality. All participants completed a 4-minute virtual realit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…Computer-generated imagery, 22,26 a 360° aspect ratio and 3-dimensional, 16-18,20 and virtual worlds 20,23 detailed the experience for the participant. Head-mounted displays were used in nearly all of the studies 16-20,22,24-28 . Hand controllers, 17,22 joy sticks, 18 screens, 20,22 and a VR facilitator 23 were also integrated as part of the experience.…”
Section: Emergent Themesmentioning
confidence: 99%
See 4 more Smart Citations
“…Computer-generated imagery, 22,26 a 360° aspect ratio and 3-dimensional, 16-18,20 and virtual worlds 20,23 detailed the experience for the participant. Head-mounted displays were used in nearly all of the studies 16-20,22,24-28 . Hand controllers, 17,22 joy sticks, 18 screens, 20,22 and a VR facilitator 23 were also integrated as part of the experience.…”
Section: Emergent Themesmentioning
confidence: 99%
“…One study reported connectivity and charging issues with equipment as well as the need for frequent software updates 26 . Training on the use of VR and financial resources for equipment were listed as challenges associated with implementation 16,27 …”
Section: Emergent Themesmentioning
confidence: 99%
See 3 more Smart Citations